Accelerated Field Durability Assessment Of Two Non-Durable Timbers (Ceiba Pentandra (L.) Gaertn. And Celtis Milbraedii Engl.) Impregnated With Natural And Inorganic Preserva-tives (Journal of Science and Technology, 2016)
Some timbers have natural resistance against decay. Others are made durable through treatment with preservatives several of which are noxious (e.g. CCA), destroy delicate body organs and are banned in many countries. Eco-friendly but efficient alternatives from organic sources including heartwood extracts of naturally durable plants are being sought. This study compares the effec-tiveness of extracts from two durable timbers (i.e. Tectona grandis L. f. (teak) and Erythro-phleum suaveolens (Guill. & Perr.) Brenan (potrodom) with three notable inorganic preserva-tives (i.e. CCA, Pyrinex 48EC and Creosote) on the field performance of two non-durable tim-bers (i.e. Ceiba pentandra (L.) Gaertn. and Celtis milbraedii Engl.). Mini-stakes (20x2x1cm) were impregnated [at 1.2bars, 123ºC for 3hrs] with 0.5% water-soluble bark extracts of T. gran-dis and E. suaveolens, CCA (0.5%), Pyrinex 48EC (0.5%) and creosote (at manufacturer’s speci-fication), and their retention in each stake determined. The stakes were then buried in the top-soil for 20 weeks. Preservative retention is less for the more viscous creosote than its water-borne counterparts. For all the durability parameters studied (i.e. visual ratings, hardness and mass losses), no significant differences (p